2016
DOI: 10.1016/j.drugpo.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Mixing drink and drugs: ‘Underclass’ politics, the recovery agenda and the partial convergence of English alcohol and drugs policy

Abstract: Where policy is concerned, academic discussion of alcohol and illicit drugs frequently emphasises their disparities. This is understandable, to a degree, as the criminal law upholds a 'great regulatory divide ' (Seddon, 2010: 56) decades. Drawing on various policy documents and commentaries, we look at recent developments relating to the control and regulation of drugs and alcohol in the broader areas of criminal justice and welfare reform. We conclude that, although the great regulatory divide remains firml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…caring responsibilities, employment). Through such neoliberal connotations, substance users were therefore demonised and stigmatised through the process of othering, as they are blamed for failing to live up to the neo-liberal notion of the productive and responsible (Lancaster et al, 2011;2015;McKendrink et al, 2008;Monaghan & Yeomans, 2016, Wincup & Monaghan, 2016. In turn, creating a distinction between the undeserving 'us ' and deserving 'them' (McKendrink et al, 2008;Monaghan & Yeomans, 2016;Taylor, 2008;Wincup & Monaghan, 2016).…”
Section: Private Residential Treatment As Best Practicementioning
confidence: 99%
See 4 more Smart Citations
“…caring responsibilities, employment). Through such neoliberal connotations, substance users were therefore demonised and stigmatised through the process of othering, as they are blamed for failing to live up to the neo-liberal notion of the productive and responsible (Lancaster et al, 2011;2015;McKendrink et al, 2008;Monaghan & Yeomans, 2016, Wincup & Monaghan, 2016. In turn, creating a distinction between the undeserving 'us ' and deserving 'them' (McKendrink et al, 2008;Monaghan & Yeomans, 2016;Taylor, 2008;Wincup & Monaghan, 2016).…”
Section: Private Residential Treatment As Best Practicementioning
confidence: 99%
“…'junkie', 'druggie', 'scum') identity (Kosovski & Smith, 2011;Neale et al, 2011). Reflecting the neo-liberal focus on achieving an authentic distinctive self through self-surveillance and control (Giddens, 1991;Harvey, 2007;Monaghan & Yeomans, 2016: Steinburg & Johnson, 2003 and the idea that a stigmatised identity can be repaired through abstinence, it was suggested that individuals do indeed have a 'true' inner self (Giddens, 1991), that differs substantially from the person they have become due to their drug use, and as such provides a convincing justification for recovery primarily through abstinence (Gibson et al, 2004;Neale et al, 2011).…”
Section: Private Residential Treatment As Best Practicementioning
confidence: 99%
See 3 more Smart Citations